On the cost of obtaining patents of invention in different countries - Hancock, W. Neilson (Statistical and Social Inquiry Society of Ireland, 1851)
In this paper I propose to direct your attention to some statistical information respecting the cost of obtaining patents or brevets of invention in different countries, which I have arranged in the following tabular form.
A paper read before the statistical section of the British Association, at Edinburgh, August 2nd, 1850.
Keywords: Patents; Copyright; 314.15